Pyroptotic and Necroptotic Cell Death in the Tumor Microenvironment and Their Potential to Stimulate Anti-Tumor Immune Responses - Scarpitta, Allan; Hacker, Ulrich T.; Büning, Hildegard; Boyer, Olivier; Adriouch, Sahil (Frontiers in Oncology, 2021)
Cancer remains the second most common cause of death worldwide affecting around 10 million patients every year. Among the therapeutic options, chemotherapeutic drugs are widely used but often associated with side effects. In addition, toxicity against immune cells may hamper anti-tumor immune responses. Some chemotherapeutic drugs, however, preserve immune functions and some can even stimulate anti-tumor immune responses through induction of immunogenic cell death (ICD) rather than apoptosis. ICD stimulates the immune system by several mechanisms including the release of damage-associated molecular patterns (DAMPs) from dying cells. In this review, we will discuss the consequences of inducing two recently characterized forms of ICD, i.e.pyroptosis and necroptosis, in the tumor microenvironment (TME) and the perspectives they may offer to increase the immunogenicity of so called cold tumors and to stimulate effective anti-tumor immune responses.